2021
DOI: 10.21037/gs-21-223
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared laparoscopy with indocyanine green for axillary sentinel lymph node biopsy in early breast cancer: preliminary experience of a single unit

Abstract: Background: A sentinel lymph node biopsy (SLNB) is a routine procedure for axillary staging in cN0 breast cancer (BC) patients. Indocyanine green (ICG) fluorescence can detect sentinel lymph nodes with higher sensitivity than carbon nanoparticle suspension (CNS). The present study investigated the availability and benefits of a near-infrared (NIR) laparoscopy-assisted SLNB using ICG and carbon nanoparticle suspension as tracers.Methods: Forty patients with invasive BC, who had clinically negative axillary lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Indocyanine green, a nonallergenic and nonradioactive fluorescent dye, has been proposed as an effective tracer for SLN identification in breast cancer. [10][11][12] It is well known that the SLN detection rates of ICG are superior to those of BD 15 ; however, the efficiency in SLN identification between ICG and RI method is controversial. Stoffels et al 16 found the use of ICG for SLN detection to be inferior compared with RI technique especially in patients in whom the lymph node basin cannot be predicted correctly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indocyanine green, a nonallergenic and nonradioactive fluorescent dye, has been proposed as an effective tracer for SLN identification in breast cancer. [10][11][12] It is well known that the SLN detection rates of ICG are superior to those of BD 15 ; however, the efficiency in SLN identification between ICG and RI method is controversial. Stoffels et al 16 found the use of ICG for SLN detection to be inferior compared with RI technique especially in patients in whom the lymph node basin cannot be predicted correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Indocyanine green, a nonallergenic and nonradioactive fluorescent dye, has been proposed as an effective tracer for SLN identification in breast cancer. 10-12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Can these be applied for non-liposuction SLNB? At present, no relevant reports have been published domestically or internationally, and only a few studies have been reported on SLNB by NIR endoscopy with the liposuction method [ 11 ]. The tumor safety of the liposuction method remains controversial [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The patient was sedated, and 10–15 min prior to surgery, 0.5 mL of 0.5 mg/mL diluted ICG solution was administered subcutaneously at the 12 o’clock and 6 o’clock positions in the areola of the affected side, and the injection site was gently rubbed for 5 min. Then, 0.5 mL of 50% CNS was injected subcutaneously at the 3 o’clock and 9 o’clock positions in the areola of the affected side, and the site was gently rubbed for 5 min [ 11 ]. The subcutaneous ICG luminous-lymphatic vessels (Fig.…”
Section: Introductionmentioning
confidence: 99%